No Political Strings Attached? The Allure of Chinese Money in Africa - Raseala, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
Usually when foreign countries invest in Africa, quite often it is expected that lucrative returns would be gained or purported practice of good governance would be used as a condition attached to the loans. Powerful and wealthy countries such as China usually loans billions of dollars to developing and weaker economies in Africa with the intention that it would influence the foreign policy of recipient countries. This could be attributed to many factors such as developing countries desperately seeking foreign direct investments to upgrade its infrastructure such as railway, roads and energy. Based on the dependency theory, this paper argues that powerful economies dictate the foreign policy of developing African economies, which they grant loans to. This paper further contends that there is no such a thing as no political strings attached. For instance, the argument is that recognising the one China policy on Taiwan is a condition. China is a newcomer in Africa and it comes with a new stand and not following the usual norm used by the World Bank and the International Monetary Fund on how it grants loans to African countries for infrastructure development. This approach is somewhat painful to other role players in the international community such as Europe; in particular Germany, United States and United Kingdom. As a result, China is moving forward towards a wiser model. This paper opted for an exploratory study using the review of literature and followed the qualitative research approach. The study found that China is alluring its money in Africa by granting huge loans to African countries for development. The study also found that China has a different culture from the one of Africa and operates different from traditional democracies in Africa. The study recommends that Africa either compete or cooperate with the Chinese economic model. It also recommends that African countries consider getting financial assistance not only from China but also from countries from Middle East such as Qatar or Saudi Arabi
Article published in the 4th Annual International Conference on Public Administration and Development Alternative03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: African economies; Foreign; Infrastructure development; International Monetary Fun; Foreign exchange; Economic policy